Generation and Detection of Optical Vortices with Multiple Cascaded Spiral Phase Plates - Ziheng Zhou; Peng Li; Jingbo Ma; Shirui Zhang; Yuzong Gu (Photonics, 2022)
Spiral phase plate (SPP) is the widely used method in the generation of vortex beam (VB) with fixed topological charges (TCs) for specific wavelength. Although VB with large TCs can be directly generated by using the SPP with high vortex order. The fabrication of high-quality SPPs with high vortex orders usually requires complex manufacturing process and high machining accuracy. An alternative method to generate VBs with large TCs is cascaded multiple SPPs with low order. In this study, we numerically calculate the transmitted light field of cascaded multiple SPPs according to the Huygens–Fresnel diffraction integral, and perform the experimental verifications. Based on cascading 6 SPPs (3 SPPs with TCs of 2, and 3 SPPs with TCs 4, respectively), an VB with TCs as high as 18 is generated. Furthermore, The TCs of the generated VB are detected by coaxial and off-axis interfering with fundamental Gaussian beam or its conjugate beam, respectively. The generated fork and spiral patterns allow us to distinguish the value and sign of TCs carried by the VB. The experimental results coincide well with the theoretical simulations. The fork pattern shows better resolution than the spiral one, and the petal pattern with small spiral allows us to distinguish large TCs with a higher resolution.